2010
DOI: 10.1111/j.1348-0421.2010.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of typical and atypical enteroaggregative Escherichia coli in Kagoshima, Japan: biofilm formation and acid resistance

Abstract: EAEC is increasingly recognized as an emerging enteric pathogen. Typical EAEC expressing the AggR regulon have been proven to be an important cause of childhood diarrhea in industrialized countries as well as in the developing world, while atypical EAEC without this regulon have not been thoroughly investigated. To investigate the bacteriological characteristics of EAEC, including both typical and atypical strains in Kagoshima, Japan, 2417 E. coli strains from Japanese children with diarrhea were screened by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 62 publications
(82 reference statements)
2
21
1
1
Order By: Relevance
“…The frequency of cefotaxime-resistance is lower than that described in other reports (24,34,35). Reportedly, the frequency of antimicrobial resistance is higher in EAEC strains isolated from symptomatic cases than from asymptomatic cases (36).…”
Section: Discussioncontrasting
confidence: 46%
“…The frequency of cefotaxime-resistance is lower than that described in other reports (24,34,35). Reportedly, the frequency of antimicrobial resistance is higher in EAEC strains isolated from symptomatic cases than from asymptomatic cases (36).…”
Section: Discussioncontrasting
confidence: 46%
“…Strains were screened for the following genes: the transcriptional regulator aggR (TOKUDA et al, 2010); cnf1 and cnf2 (BLANCO et al, 1996); the toxin genes sta, Stx1, Stx2 (multiplex PCR) (FRANCK et al, 1998); intimin (eae) (BLANCO et al, 2006); bundle-forming pili (bfpA) (GUNZBURG; TORNIEPORTH; RILEY, 1995); ipaH for EIEC (ARANDA et al, 2007); Stx2e, the most frequent pathovar identified, F41, stb, LT, 987P, F18, K88, and K99 (multiplex PCR) (MACÊDO et al, 2007). The PCR reaction conditions were performed according to each author, with no modifications.…”
Section: Detection Of Virulence Genes and Characterization Of Phylogementioning
confidence: 99%
“…E. coli strains that produce the CTX-M type of ESBLs are increasingly being isolated from adults and children with UTIs and bacteremia; however, CTX-M ESBLs have rarely been found among diarrheagenic E. coli (DEC) strains. We previously reported that 36.8% of the aggR gene-positive EAEC strains isolated from diarrheal children in Kagoshima, Japan, were cefotaxime resistant (22), suggesting ESBL production. Subsequently, some CTX-M-producing EAEC strains were reported worldwide (23)(24)(25)(26), including an EAEC-Shiga toxin-producing E. coli (STEC) hybrid clone of O104:H4 that caused a large outbreak in Germany in 2011 (27).…”
mentioning
confidence: 99%